Trade network characteristics, competitive patterns, and potential risk shock propagation in global aluminum ore trade - Wang, Yue; Chen, Lu; Wang, Xiaoyi; Tang, Nan; Kang, Xinyu (Frontiers in Energy Research, 2023)
Aluminum is an essential strategic mineral resource. The geographical space distribution characteristics make the aluminum ore trade relationship more complicated. This paper analyzes the evolution characteristics, spatial migration, and trade competition of aluminum ore trade from 2011 to 2020. This paper constructs the aluminum supply risk propagation network (ASRSN) to analyze the propagation path, impact scope, and potential impact of different risk outbreak sources. The results show that a few countries control more aluminum ore resources, and the trade community and center of trade gravity have changed significantly. Trade competition gradually intensifies, mainly concentrated in Asia and Europe. When supply risk occurs, the threat spreads rapidly. This paper selects four major trading countries Brazil, Guinea, Australia, and China, as risk outbreak countries. Risk outbreak mainly shows three typical characteristics. Meanwhile, indirect infections account for a large proportion, and China plays an essential role in trade. Finally, based on these findings, some suggestions to maintain the stability of the aluminum resource trade and improve its ability to resist risks for China.